Two Unpublished Poems on the Battle of Banja Luka From Kadic’·S Chronicle - Hadžiosmanović, Lamija (Prilozi za orijentalnu filologiju, 2017)
In the well-known Kadić Chronicle consisting of twenty-eight volumes the autograph is kept in the Gazi Husrevbeg Library in Sarajevo), the author has also found these two poems. The first one is a chrono-verse panegyric dedicated to· the commander in the Battle of Banja Luka, Ḥekim oġlu 'Ali-paša, composed by Abdullah Kantamiri-zade of Sarajevo. The poet composed this eulogy in twenty distiches in the most frequently used meter: Fā'hlātün Fa'ilātün Fā'ilün. The poem has all the characteristics of divan poetry and as far as its form is concerned it is beyond rep roach. It is written in Turkish with a lot of customary Arabic and Persian constructions and expressions. The poet’s view of Ali-pasha goes beyond the limits of the objective facts and therefore deviates considerably from history. The second poem was recorded as the work of an unknown author. It greatly differs from Kantamiri-zade's poem in both form and style. It is simpler and more understandable. In form, and especially in language, it reminds one of folk poetry. These elements made it popular and it is supposed that it was sung by common people as well. The poet speaks mainly about the battle, devoting to Ali-paša Ḥekim oġlu a reasonable and objective amount of space. The poet's attitude to historical facts is much more realistic. The poem contains twenty quadristichs in a fairly correct Turkish, without a flowery style or expressions.